X-linked inhibitor of apoptosis positive nuclear labeling: a new independent prognostic biomarker of breast invasive ductal carcinoma - Peng Bofang; Zhou Hongyuan; Li Feng; Tang Yun; Zhu Jianhua; Zhang Yutao; Zhou Chifeng; Fu Rong (BMC, 2011)
Abstract Background It's well recognized that X-linked inhibitor of apoptosis (XIAP) was the most potent caspase inhibitor and second mitochondria-derived activator of caspase (Smac) was the antagonist of XIAP. Experiments in vitro identified that down regulation of XIAP expression or applying Smac mimics could sensitize breast cancer cells to chemotherapeutics and promote apoptosis. However, expression status and biologic or prognostic significance of XIAP/Smac in breast invasive ductal carcinoma (IDC) were not clear. The present study aimed to investigate relationship among expression status of XIAP/Smac, apoptosis index (AI), clinicopathologic parameters and prognosis in IDC. Methods Immunohistochemistry and TUNEL experiment were performed to detect expression of XIAP, Smac, ER, PR, HER2 and AI in 102 cases of paraffin-embedded IDC samples respectively. Expression of XIAP/Smac were also detected in limited 8 cases of fresh IDC specimens with Western blot. Results Positive ratio and immunoscore of XIAP was markedly higher than Smac in IDC (P < 0.0001). It was noteworthy that 44 cases of IDC were positive in nuclear for XIAP, but none was for Smac. Expression status of Smac was more prevalent in HER2 positive group than negative group (P < 0.0001) and AI was positively correlated with HER2 protein expression (rs = 0.265, P = 0.017). The present study first revealed that XIAP positive nuclear labeling (XIAP-N), but not cytoplasmic staining (XIAP-C), was the apoptotic marker correlated significantly with patients' shortened overall survival (P = 0.039). Survival analysis demonstrated that XIAP-N was a new independent prognostic factor except for patient age and lymph node status. Conclusion Disturbed balance of expression between XIAP and Smac probably contributed to carcinogenesis and XIAP positive nuclear labeling was a new independent prognostic biomarker of breast IDC.